2014
DOI: 10.1096/fj.13-243733
|View full text |Cite
|
Sign up to set email alerts
|

The importance of being a lumen

Abstract: Advances in tissue engineering and microtechnology have enabled researchers to more easily generate in vitro tissue models that mimic the tissue geometry and spatial organization found in vivo (e.g., vessel or mammary duct models with tubular structures). However, the widespread adoption of these models for biological studies has been slow, in part due to the lack of direct comparisons between existing 2-dimensional and 3-dimensional cell culture models and new organotypic models that better replicate tissue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 45 publications
2
55
0
Order By: Relevance
“…This may be due to concentration gradients of soluble factors, cell adhesion, and mechanical forces . Similarly, we have observed a considerable change in cytokine secretion by both endothelial cells and epithelial cells when cultured in an in vivo‐like structure (i.e., a lumen) compared to 2D and 3D cultures . Lumens (i.e., tubular structures) are ubiquitous in vivo being present in blood vessels, mammary ducts, and the lymphatic system.…”
mentioning
confidence: 51%
“…This may be due to concentration gradients of soluble factors, cell adhesion, and mechanical forces . Similarly, we have observed a considerable change in cytokine secretion by both endothelial cells and epithelial cells when cultured in an in vivo‐like structure (i.e., a lumen) compared to 2D and 3D cultures . Lumens (i.e., tubular structures) are ubiquitous in vivo being present in blood vessels, mammary ducts, and the lymphatic system.…”
mentioning
confidence: 51%
“…Organotypic design is more than cosmetic: the importance of cell–cell interactions and structure/function relationships is well established . It has even been demonstrated that structure and geometry alone alters endothelial and epithelial cell soluble factor signaling and phenotype . In the study of the innate immune response, for example, it has been shown that multiculture, cell–cell signaling, and cell–matrix interactions alter neutrophil transendothelial migration, chemotaxis behavior, and surface marker expression .…”
Section: Introductionmentioning
confidence: 99%
“…Misalignment and seams will lead to discontinuities in the wall, disturbing the flow and adhesion of endothelium. The layer-by-layer fabrication also results in predominantly square shaped channels that do not resemble the in vivo round lumen shape that is critical for normal functioning [52]. Either high resolution techniques are required to create round channels on the micrometre scale of the vasculature or post processing must be applied to reshape the square channels into round ones.…”
Section: Layer-by-layer Compositionmentioning
confidence: 99%